Implementasi kebijakan Peraturan Gubernur Nomor 58 Tahun 2020 tentang Karang Taruna di Kota Manado Provinsi Sulawesi Utara - Billy Lombok; Sisca Beatrix Kairupan; Steven Tarore (Lembaga Penelitian dan Pengabdian Universitas Negeri Manado, 2022)
Implementation of the policy of Governor Regulation Number 58 of 2020 concerning Karang Taruna in Manado City, North Sulawesi Province. Karang Taruna is one of the nation's strengths that has the potential to be developed to build the nation and state. Karang Taruna Sulawesi Utara works based on Peraturan Gubernur Nomor 58 Tahun 2020 concerning Karang Taruna Provinsi Sulawesi Utara. This study aims to describe and analyze the implementation of the policy of this regulation, along with its supporting and inhibiting factors. The author found that there were mismanagement of Karang Taruna of the City of Manado who did not understand well their functions as members of Karang Taruna, namely apathy or indifference in holding the position of Karang Taruna administrators, there were no plans to carry out their functions, in carrying out the functions of Karang Taruna, and do not have programs or activities so that regional regulations are not implemented properly. The inhibiting factors in the implementation process include communication, resources, attitudes, and bureaucratic structures